Algebraic communication channels - Leontiev, V. K.; Movsisyan, Gh. L. (Armenian Journal of Mathematics, 2008)
Modern information theory studies various communication channels modelling certain situations. The basic matter of the present research is the information transmission process from Ð° source to Ð° receiver, and main parameters are the throughput/carrier capacity/transmission capacity and the information transmission speed.